Acupressure Reducing Complaints Of Nausea And Vomiting Patient With Tuberculosis - Hesti Platini; Sandra Pebrianti; Kosim Kosim (Journal of Nursing Care, 2021)
Adverse effects of pulmonary tuberculosis treatment that often arise in the first month are nausea. This effect causes the occurrence of non-compliance with taking anti-tuberculosis drugs. For this reason patients with tuberculosis need non-pharmacological management such as acupressure. Acupressure is a mechanical or compressive manipulation based on one or more movements of certain meridians or points. This study aims to determine the effect of acupressure on nausea and vomiting in pulmonary tuberculosis patients due to the effects of pharmacology. The method was used quantitative design with a quasi-experimental design with pre-test and post-test with group control. The measuring instrument for nausea and vomiting was the Rhodes Index of Nausea Vomiting and Retching. The population was all pulmonary tuberculosis patients in category 1 treatment. The sample technique used is consecutive sampling. Sampling was consisted complaining nausea with or without vomiting. Data was analysis using t-test. The results was showed significant difference before and after the intervention to reduce nausea and vomiting (p = 0.000). Acupressure is a complementary therapy that can effectively reduce complaints of nausea and vomiting in pulmonary tuberculosis patients which is carried out at points P 6 and St 36 for 15 minutes. This research can be used as a recommendation for applying complementary acupressure therapy in providing nursing care to tuberculosis patients